Ruwad Aslimat Wilayat Sunda fi Al-Qarn Ar-Rabi‘ Asyr fi Manzhur An-Nushush At-Tarikhiyah - Izzuddin Musthafa; Suparman Suparman (UIN Maulana Malik Ibrahim Malang, 2018)
ووفقا لمصادر التاريخ المحلية سواء أ كانت شفوية ام كتابية، فكان الرواد الأوائل في نشر دين الإسلام في أرض باسوندان (Pasundan)، هم ثلاثة أشخاص من أبناء ملك باججرن (Pajajaran) : الأمير جكرابوانا (Cakrabuana) وشريف هداية الله (Syarif Hidayatullah) ، وملك كيان سانتانج (Kean Santang). بالرغم من أن معظم المؤرخين يشكون في وجودهم ودور هؤلاء الثلاثة لكثرة عدد الأسماء التي نسبـت إليهم، والخطأ في أخذ المصادر، ولكثرة الأساطير التي تم العثور عليها في المصادر المحلية. واستنادا إلى الواقع التاريخي هذا، فإن هذه الورقة هي محاولة لكشف الغموض أو عدم وضوح الموقف، والوظيفة، ودور الشخصيات الثلاثة في عملية الأسلمة في أرض باسوندان.الطريقة المستخدمة في هذا البحث هو الطريقة التاريخية-السيميائية باستخدام النصوص كمصدر للمعلومات. النصوص المستخدمة هي المخطوطات الآتية:Naskah Negara Kretabhumi, Carita Purwaka Caruban Nagari, Babad Cerbon, Sajarah Cerbon, Sajarah Babad Nagari Cerbon, Babad Sunan Gunung Djati, Wawacan Sunan Gunung Djati, Babad Walangsungsang, Sajarah Lampahing Para Wali Kabeh, Wawacan Prabu Kean Santang dan Babad Limbangan.اتضحت النتائج أن الرواد الأوائل في نشر الإسلام في الساحل الشمالي لمنطقة شيريبون (Cirebon)هو العالم شريف هداية الله أي سونان غونونج جاتي(Sunan Gunung Djati).According to local history sources both oral and written, early pioneer for spreading Islam in Tatar Pasundan are three royal Pajajaran, namely the Pangeran Cakrabuana, Prabu Kean Santang and Syarif Hidayatullah. However, most chroniclers doubted the existence and the role of three characters because of the many names which are used to them, error in citing, and many myths related to them. This paper will try to unravel the mystery, function, and role of three characters in the process of Islamization in the Tatar Pasundan. The method used in this study is the historical method. The texts used are Manuscripts of Negara Kretabhumi, Carita Purwaka Caruban Nagari, Babad Cerbon, Cerbon history, history of Nagari Cerbon Babad, Babad Sunan Gunung Djati, Wawacan Sunan Gunung Djati, Babad Walangsungsang, the history of Lampahing Parawali Kabeh, Wawacan Kean Santang and Babad Limbangan. The results show that the first pioneers of spreading Islam in the coastal north of Cirebon were the prince Kean Santang, and Syarif Hidayatullah (Sunan Gunung Djati).